Prinsip Kepemilikan Hak pada Pembebanan Jaminan Fidusia - Nanang Suparto (Fakultas Hukum Universitas Islam Jember, 2015)
Agreements consumer financing PT Summit Oto Finance Branch Jember issued by financial institutions is in the making must meet the legality contained in treaty law, but agreements consumer financing issued by PT Summit Oto Finance Branch Jember not meet a legal agreement because there is an object burdened by two collateral material and breach of contract clauses that are not in accordance with Code Article 1337 of the Civil Code. In consumer financing agreement PT Summit Oto Finance Branch Jember include collateral objects burdened by fiduciary yet burdened fiduciary object is not made with the fiduciary deed and registered at the registration office Fiduciary. In Act No. 42 of 1999 on fiduciary clearly said that the objects were burdened by the fiduciary must be made with the fiduciary deed and registered at the registration office so that it can be said fiduciary in consumer financing agreement PT Summit Oto Finance Branch Jember there is not a guarantee. In consumer financing agreement if the debtor is said to commit a breach of contract late in paying the installments vehicle then the creditor can take the vehicle by force based on a power of attorney. Supposedly, if the debtor did breach the creditor may file a complaint with the local court to make a confiscation made by bailiff or using a system of mediation conducted by mediators.